Alcathoe bat (Myotis alcathoe) in the Czech Republic: distributional status, roosting and feeding ecology - Lučan, Radek (Jihočeská univerzita, 2010)
Between 2001 and 2008, we recorded Myotis alcathoe at nine sites within three distant areas in the Czech Republic. The species identification was confirmed with cyt b sequences and four distinct haplotypes were identified. All the localities exhibit surprisingly uniform habitat characteristics: (1) old full-grown oak-hornbeam forests, with (2) numerous large trees in advanced stages of decay are present, and (3) a very small to large water bodies and/or patches of riparian vegetation surrounded by the forest. Using radiotracking techniques, we discovered 27 day roosts of M. alcathoe, located mostly in big oak, birch and lime trees inside extensive forest stands. All roosts were fissures or small cavities in a tree trunk and in branches in the canopies, some 16 m above the ground. Bats preferred trees that were higher, had higher canopy and canopy basement and had larger diameter at breast height than other available trees. Roost trees were surrounded by lower trees with lower canopy basements than available trees. Roost trees were in a poorer condition than other available trees. Roosts were occupied by up to 83 individuals in July but usually single individuals were found in the roosts in September. In contrast to syntopic M. mystacinus and M. brandtii, M. alcathoe has never been found in an anthropogenic roost (except for a fissure in concrete electricity pole). Preliminary analysis of the diet showed that nematoceran flies were the most important prey item along with spiders, caddis flies, small moths and neuropterans. In the observed ecological characteristics, M. alcathoe markedly differs from other European species of the genus Myotis. Its restricted habitat requirements are perhaps responsible for an islet-like pattern of its distribution and suggest an essential conservation value of the habitats of its occurrence.
Alcathoe bat (Myotis alcathoe) in the Czech Republic: distributional status, roosting and feeding ecology
Keywords: radio tracking; diet analysis; tree roosts; forest bats; Myotis alcathoe; radio tracking; diet analysis; tree roosts; forest bats; Myotis alcathoe